Data envelopment analysis for profitability and marketing in the 10 largest banks in Indonesia - JMV Mulyadi (STIE Perbanas Surabaya, 2019)
The higher competition in banking industry has pushed the banks to increase efficiency both their profitability and marketing. This study aims to assess the efficiency of the 10 largest banks in Indonesia both in terms of profitability and marketing period 2017-2018 using the Data Envelopment Analysis (DEA) method. The results show that from 2017 to 2018, there were 7 banks that consistently obtained good profitability levels. The average bank profitability performance decreased from 2017 to 2018. From the marketing side, with the first input approach, during 2017-2018 there were only 6 banks that consistently obtained good levels of efficiency, while with the second input approach, there were only 5 banks that consistently achieved good efficiency. The average bank marketing performance declined from 2017 to 2018 using the first and second approaches. In general, bank performance in marketing is still below the bank performance in profitability. The implication is that in using DEA, it must be wise in selecting the input variables because they will produce different values.